Ameliorating Conflicts Of Interest In Auditing: Effects Of Recent Reforms On Auditors And Their Clients - Nelson, Mark W. (Academy of Management Review, 2006)
Moore, Tetlock, Tanlu, and Bazerman conclude that recent auditing reforms are misguided and insufficient. I argue that Moore et al. do not consider sufficiently how recent reforms reduce the likelihood of audit failure by affecting the incentives and actions of audit clients as well as auditors. I conclude that further research is necessary to understand the effects (both intended and unintended) of recent reforms before enacting further reforms.